2016
DOI: 10.1093/toxsci/kfw041
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Environmental Quaternary Ammonium Compounds as Direct Inhibitors of Cholesterol Biosynthesis

Abstract: In this study, we aim to identify environmental molecules that can inhibit cholesterol biosynthesis, potentially leading to the same biochemical defects as observed in cholesterol biosynthesis disorders, which are often characterized by congenital malformations and developmental delay. Using the Distributed Structure-Searchable Toxicity (DSSTox) Database Network developed by EPA, we first carried out in silico screening of environmental molecules that display structures similar to AY9944, a known potent inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 62 publications
4
55
1
Order By: Relevance
“…The lipidomic results on BAC-exposed Neuro2a cells are consistent with our previous studies on the biological activities of individual BACs (47). Because BAC-C10 acts as a potent inhibitor of DHCR7, we anticipated that the effects of AY9944 and BAC-C10 treatments on the Neuro2a lipidome would be similar.…”
Section: Bac Exposure Alters Lipid Homeostasissupporting
confidence: 88%
See 4 more Smart Citations
“…The lipidomic results on BAC-exposed Neuro2a cells are consistent with our previous studies on the biological activities of individual BACs (47). Because BAC-C10 acts as a potent inhibitor of DHCR7, we anticipated that the effects of AY9944 and BAC-C10 treatments on the Neuro2a lipidome would be similar.…”
Section: Bac Exposure Alters Lipid Homeostasissupporting
confidence: 88%
“…In the context of elevated phospholipid levels, the decreased DG levels in BAC-C16 treatment suggest increased glycerophospholipid biosynthesis from DGs rather than decreased DG synthesis. In our previous study, gene expression analysis revealed that fatty acid synthase was significantly upregulated in BAC-C16-treated Neuro2a cells (47), which is consistent with the elevated phospholipid levels observed in BAC-C16 treatment.…”
Section: Bac Exposure Alters Lipid Homeostasissupporting
confidence: 82%
See 3 more Smart Citations